THE AMBIVALENT PORTRAYAL OF THE ECOFEMINIST MOVEMENT IN TANAH IBU KAMI (2020) - Zhafirah, Faizzah Shabrina; Priyatna, Aquarini; Adipurwawidjana, Ari Jogaiswara (Universitas Padjadjaran, 2023)
Tanah Ibu Kami (2020), a documentary film produced by The Gecko Project and Mongabay, published on YouTube, follows the travels of journalist Febriana Firdaus to four rural areas in Indonesia where she meets Sukinah from Kendeng, Central Java; Lodia Oematan and Aleta Baun from Mollo, East Nusa Tenggara; Eva Bande from Banggai, Central Sulawesi; and Farwiza from Banda Aceh, Aceh. The film portrays these women leading socio-ecological movements that fight for their rights along with their land rights, as they face the risks of violence, imprisonment, and judgment from large corporations and patriarchal customs and beliefs. Placing the documentary within the ecofeminist framework, exemplified by Warren (2000) and Shiva and Mies (2018), I would like to show how the documentary portrays the state and the cultural institutions having control over women and nature. In its narrative method, the film tends to look at the environmentalism done by women as something to be highlighted not because of its substantial aspects but more as a valorized act because of its masculine attributes. Thus, while the film glorifies women as empowered environmentalists with the ability to exert agency, the structure of and behind the film is based on patriarchal assumptions.